EDUKASI HIDUP SEHAT PADA ANAK DENGAN BERKEBUN SAWI HIJAU DI SDIT INSANURRAHMAN KELURAHAN LOKTABAT UTARA KOTA BANJARBARU (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
In social life, we can observe that children are less fond of foods made from vegetables. The Proportion of Consumption of Fruits/Vegetables Per Day of the Week in Population Age 5 Years According to the Characteristics of South Kalimantan Province, Riskesdas 2018, 34.56% of children aged 5-9 years do not consume vegetables and fruit. Also, for children aged 10-14 years, as much as 27.68% do not consume fruits and vegetables. This figure is high compared to other age groups. When the service was carried out, the average Pretest score was 8.21, which means that the students had a fairly good knowledge of healthy living education, and the average Post-Test was 8.5. Based on this value, there is an increase in the average knowledge of students after being given counselling. It is known that respondents' pre-test and post-test scores are generally not distributed because the significant value is less than 0.05 (Pre-test Sig Value = 0.001
Keywords: Children; Healthy; Mustard greens; gardening